2019
DOI: 10.1002/jcp.28647
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines associated with cancer growth induce mitochondria and cytoskeleton alterations in cardiomyocytes

Abstract: Cardiac dysfunction is often observed in patients with cancer also representing a serious problem limiting chemotherapeutic intervention and even patient survival. In view of the recently established role of the immune system in the control of cancer growth, the present work has been undertaken to investigate the effects of a panel of the most important inflammatory cytokines on the integrity and function of mitochondria, as well as of the cytoskeleton, two key elements in the functioning of cardiomyocytes. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 63 publications
4
28
0
Order By: Relevance
“…It can increase the levels of pro‐inflammatory interleukins such as IL‐8 and IL‐6 (Elsea, Roberts, Druker, & Wood, 2008). However, these changes depend on the types of cancer cells, the dose of DOX (usually needs a dose >5 mg/kg), and receiving complementary drugs (Buoncervello et al., 2019). In human small‐cell lung cancer cell lines, DOX increased the production of IL‐8.…”
Section: Discussionmentioning
confidence: 99%
“…It can increase the levels of pro‐inflammatory interleukins such as IL‐8 and IL‐6 (Elsea, Roberts, Druker, & Wood, 2008). However, these changes depend on the types of cancer cells, the dose of DOX (usually needs a dose >5 mg/kg), and receiving complementary drugs (Buoncervello et al., 2019). In human small‐cell lung cancer cell lines, DOX increased the production of IL‐8.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Frangogiannis et al revealed that CCL2 and CXCL8 were markedly increased in the infarcted myocardium and might regulate leukocyte infiltration and granulation tissue formation [ 41 ]. Besides, the upregulation of CXCL8 in CMs could lead to damage of actomyosin cytoskeleton distribution and mitochondrial network organization [ 42 ]. AP-1 (c-JUN/c-FOS) was also reported to be involved in cardiac remodeling, myocardial dysfunction and progression of heart failure [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transport of the GnRH transcript to the nerve terminals in the ME requires the integrity and proper functioning of cytoskeletal elements. Increasing evidence suggests that inflammatory cytokines induce cytoskeleton rearrangements in various cells such as cardiomyocytes, intestinal epithelium, or breast cancer cells [71][72][73]. Cytoskeleton organization is also affected by cytokines in neurons.…”
Section: Mechanisms Of Lps-induced Anti-gonadotropic Effect Of Inflammentioning
confidence: 99%